Linking the Community Health Fund with Accredited Drug Dispensing Outlets in Tanzania: exploring potentials, pitfalls, and modalities - Angel Dillip; Albino Kalolo; Iddy Mayumana; Melina Rutishauser; Vendelin T. Simon; Brigit Obrist (Taylor & Francis Group, 2022)
Background In low- and middle-income countries, too, public-private partnerships in health insurance schemes are crucial for improving access to health services. Problems in the public supply chain of medicines often lead to medicine stock-outs which then negatively influence enrolment in and satisfaction with health insurance schemes. To address this challenge, the government of Tanzania embarked on a redesign of the Community Health Fund (CHF) and established a Prime Vendor System (Jazia PVS). Informal and rural population groups, however, rely heavily on another public-private partnership, the Accredited Drug Dispensing Outlets (ADDOs). This study takes up this public demand and explores the potentials, pitfalls, and modalities for linking the improved CHF (iCHF) with ADDOs. Methods This was a qualitative exploratory study employing different methods of data collection: in-depth interviews, focus group discussions, and document reviews. Results Study participants saw a great potential for linking ADDOs with iCHF, following continuous community complaints about medicine stock-out challenges at public health facilities, a situation that also affects the healthcare staff's working environment. The Jazia PVS was said to have improved the situation of medicine availability at public health facilities, although not fully measuring up to the challenge. Study participants thought linking ADDOs with the iCHF would not only improve access to medicine but also increase member enrolment in the scheme. The main pitfalls that may threaten this linkage include the high price of medicines at ADDOs that cannot be accommodated within the iCHF payment model and inadequate digital skills relevant for communication between iCHF and ADDOs. Participants recommended linking ADDOs with the iCHF by piloting the connection with a few ADDOs meeting the selected criteria, while applying similar modalities for linking private retail outlets with the National Health Insurance Fund (NHIF). Conclusions As the government of Tanzania is moving toward the Single National Health Insurance Fund, there is a great opportunity to link the iCHF with ADDOs, building on established connections between the NHIF and ADDOs and the lessons learnt from the Jazia PVS. This study provides insights into the relevance of expanding public-private partnership in health insurance schemes in low- and middle-income countries.